Pharmacological evidence for beta(2)-adrenoceptor in right atria from stressed female rats - Spadari-Bratfisch, R. C.; Santos, I. N.; Vanderlei, LCM; Marcondes, F. K. (Natl Research Council Canada, 1999)
The purpose of the present study was to demonstrate a physiological response to TA2005, a potent beta(2)-adrenoceptor (beta(2)-AR) selective agonist, in right atria isolated from stressed female rats under the influence of the estrous cycle. We obtained concentration-response curves to the agonist in the presence and in the absence of selective antagonists in right atria isolated from female rats submitted to three daily foot-shock sessions (30 min duration, 120 pulses of 1.0 mA, 1.0 s, applied at random intervals of 5-25 s) and sacrificed at estrus or diestrus. Our results showed that the pD(2), values of TA2005 were not influenced by estrous cycle phase or foot-shock stress. However, in right atria from stressed rats sacrificed during diestrus, the concentration-response curve to TA2005 was biphasic, with a response being obtained at concentrations of 0.1 nM, whereas during estrus no response was observed at doses lower than 3 nM. ICI118,551, a beta(2)-AR antagonist, abolished the response to nanomolar concentrations of TA2005 in right atria from stressed rats at diestrus, with no changes in a,agonist pot values in right atria from control rats (7.47 +/- 0.09, p > 0.05) but a 3-fold decrease in pD(2), values of TA2005 in right atria from foot shock stressed rats (7.90 +/- 0.07, p less than or equal to 0.05). Concentration-response curves to TA2005 in the presence of ICI118,551 were best fitted by a one-site model equation. The beta(1)-AR antagonist, CGP20712A, shifted to the right only the second part of the concentration-response curves to the agonist, unmasking the putative Pz-AR-mediated response to the agonist in tissues isolated from stressed rats at diestrus. Under this condition, concentration-response curves to the agonist were best fitted by a two-site model equation. pot and maximum response of TA2005 interaction with beta(1)- and putative Pz-adrenoceptor components were calculated. Schild analyses gave a pK(B) value for CGP20712A that was typical for the interaction with beta(1)-AR in each experimental group. pK(B), values for ICI118,551 could not be obtained in stressed rats sacrificed at diestrus since Schild plot slopes were lower than 1.0. In right atria from control rats, ICI118,551 pK(B), values were similar to reported values for the interaction of the antagonist with beta(1)-AR. These results confirm that a heterogenous PAR population mediating the chronotropic response to catecholamines can be demonstrated in right atria from foot shock stressed female rats sacrificed at diestrus. The stress-induced response seems to be mediated by the beta(2)-AR subtype. Right atria from rats sacrificed during estrus are protected against stress-induced alterations on the homogeneity of PAR population.
Keywords: foot-shock stress; TA2005; ICI118,551; CGP20712A; estrus; diestrus